1996
DOI: 10.1002/(sici)1097-0215(19960703)67:1<54::aid-ijc11>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte-macrophage-colony-stimulating factor enhances immune responses to melanoma-associated peptidesin vivo

Abstract: o 1996 Wiley-Liss, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
109
0
4

Year Published

1998
1998
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(115 citation statements)
references
References 22 publications
(22 reference statements)
2
109
0
4
Order By: Relevance
“…Our data support the results of Jaeger et al, 22 who found enhanced DTH and CTL responses after i.d. peptide immunization in combination with systemic GM-CSF administration.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data support the results of Jaeger et al, 22 who found enhanced DTH and CTL responses after i.d. peptide immunization in combination with systemic GM-CSF administration.…”
Section: Discussionsupporting
confidence: 93%
“…in combination with granulocyte-macrophage colony-stimulating factor (GM-CSF) has been reported to induce efficient T-cell responses against peptide antigens in experimental animals 21 and to enhance T-cell responsiveness to melanoma-associated peptides in melanoma patients and patients with breast and ovarian carcinomas. 22,23 The adjuvant effect of the cytokine GM-CSF is related to the maturation and activation of DCs, which after antigen uptake will move to an adjacent lymph node and activate effector T cells. 16,17,24 To induce anti-ras immunity in patients with pancreatic cancer, we developed a vaccination protocol based on i.d.…”
Section: Abstract: Peptide Vaccination; Pancreatic Cancer; Mutant Ramentioning
confidence: 99%
“…Although immunization with tumor-antigen derived peptides did not induce immune responses, the concomitant administration of GM-CSF elicited delayed type hypersensitivity and T-cell responses [30,31]. The potential of GM-CSF to support the differentiation of monocytes into DCs as a single factor may at least in part be involved in enhancement of the immunological effects induced by the vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…GM-CSF is a commercially available cytokine currently used in patients undergoing chemotherapy to shorten the duration of post-chemotherapy neutropenia. Recently published evidence also suggests that GM-CSF plays an important role as an immune adjuvant [42,43]. The following observations illustrate the mechanisms by which GM-CSF can potentiate the immunogenicity of an antigen: 1) GM-CSF is a key mediator of DC maturation and function [44]; 2) GM-CSF increases surface expression of class I and II MHC molecules as well as costimulatory molecules of DCs in vitro [44]; 3) GM-CSF enhances antibody responses to known immunogens in vivo [45]; 4) tumor cells transfected with genes encoding/expressing GM-CSF are able to induce long lasting, specific anti-tumor immune responses in vivo [46]; and 5) GM-CSF encapsulated in biodegradable microspheres mixed with whole tumor cells resulted in systemic anti-tumor immune responses comparable to those of GM-CSF transfected tumor cells [47].…”
Section: Introductionmentioning
confidence: 99%